Screening of psychiatric morbidity in a male only prison - Parajuli, Sujana (Journal of Patan Academy of Health Sciences, 2023)
Introduction: Psychiatric morbidities such as anxiety and depression are disproportionately higher among prisoners than in general population. Around one in seven prisoners are diagnosed with psychosis or depression. The chronicity of psychiatric morbidities may lead to suicidality among prisoners. Thus, the aim of this study was to screen psychiatric morbidity in a male only prison.Method: This was cross-sectional analytical study done at Nakkhu Jail in Nepal. A total of 490 prisoners selected by total enumerative sampling were interviewed face-to-face. Modified Mini Screen was used to find out psychiatric morbidities. Data analysis was done using frequency, percentage, mean and standard deviation. Association and correlation between information related to prisoners and environmental variables and psychiatric morbidity were analyzed using Chi-square and Spearman’s rank correlation coefficient test respectively.Result: The psychiatric morbidity was found positive among 10.41% of prisoners. Suicidality was present among 3.47% of prisoners and 3.06% had post-traumatic stress disorder. There was significant association between length of stay in prison (p=0.026), satisfaction on living facilities (p=0.017), regular health check-up (p